Legal Policy on Gambling Crime - Dany Rimawan; Faisal Santiago; Azis Budianto (Publikasiku, 2023)
Gambling is a form of social pathology that poses a real and potential threat to social norms so that it threatens social order. Thus, it will greatly impact on national development with material-spiritual aspects which must therefore be addressed in a rational way. One of these rational efforts is the policy approach to criminal law enforcement regulated in the Criminal Code (KUHP) in accordance with the amendments by Law no. 7 of 1974 concerning the regulation of gambling. However, the policy formulation of laws and regulations has several weaknesses. At the applicative stage, the judge is not free to determine the types of criminal sanctions that will be imposed on the perpetrators of gambling crimes. This is due to the general minimum system and the general maximum system adopted by the Criminal Code, so that any type of criminal sanctions contained in the law must be applied by judges. Policies for dealing with gambling crimes in the future must still be carried out by means of a penalty. Policy formulation of criminal law must be more optimal and able to reach the development of criminal acts of gambling with advanced technology.